TINGKAT KEPERCAYAAN MASYARAKAT TERHADAP PASLON (PASANGAN CALON) TUNGGAL DALAM PILKADA WALIKOTA MAKASSAR 2018 DI TINJAU DARI HUKUM TATA NEGARA ISLAM - Suhardimang, Suhardimang; Daeng Mapuna, Muhammad Hadi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
Observational research on the phenomenon of a single candidate in the 2018 Mayor and Deputy Mayor of Makassar post-conflict local election contestation is viewed from the perspective of Islamic constitutional law. The next issue is broken down into sub-problems or research questions, namely: How does the Election Law affect single candidate pairs in the 2018 simultaneous regional elections; What is the perspective of the people of Makassar on the phenomenon of the emergence of a single candidate pair in the 2018 Makassar Mayor Election? This type of research is classified as a qualitative descriptive Fieldreseach with the research approaches used, namely: juridical and empirical. The data source of this research is primary data, researcher interviews with informants in this case the community. Secondary data obtained from books, literature, and documents related to this research problem. Furthermore, the data collection methods used are observation, interviews, documentation, and literature study. Then the data processing and analysis techniques were carried out through three stages, namely: organizing the data, analyzing data, and interpreting data or drawing conclusions. The results of the research obtained answers to existing problems and draw conclusions, first the points relating to single partners found in Article 54 to Article 55 of Law No.10 of 2016. In this article, it shows that Law No.10 of 2016 has an influence on Spouses candidates, where a single candidate, which was not originally regulated in the previous Pilkada Law, is then presented as an alternative for the KPU as the implementer of the Pilkada Law so that they can continue to run Pilkada in an area without having to delay the consequences of a single contestant in the Pilkada. Keywords: Single Pair; Contestation; Empty Box; Regional Head Election;